Scabies Treatment in Children: A Narrative Review - Armaghan Kazeminejad; Zohreh Hajheydari; Mohammad Jafar Ghahari (Mazandaran University of Medical Sciences, 2019)
Context: Scabies is a common infestation in children. Treatment of scabies in infants and children is a therapeutic challenge. Many prescribed drugs for adults cannot be used in children because of their side effects and safety profile. This review article studied the treatment of scabies in children and infants.  Evidence Acquisition: In this review, electronic databases, including Google Scholar, PubMed, Cochrane and Scopus were searched based on the following MeSH terms: Scabies, Pediatric and Children. We included all articles related to scabies in children published from 2008 to 2018. Duplicated and irrelevant studies and abstracts were excluded. Results: The management of scabies is focused on identification and treatment of cases and household contacts. We briefly discussed the clinical presentation of scabies with the currently used topical and oral treatments for this infestation. Topical treatments are effective and the most effective treatment is permethrin. Other treatment options may be less effective, poorly tolerated, or with adverse effects. Conclusions: Scabies is prevalent in children and causes considerable morbidity. Because of its complications, scabies should be managed properly in accordance with the guidelines.